PERAN SEMANTIS DAN RELASI GRAMATIKAL VERBA DATIVE BAHASA BALI: PENELITIAN CORPUS LEIPZIG - Dwipayana, Ida Bagus Janardana (Prosiding Seminar Nasional Bahasa Ibu; Vol 2 No 1 (2025): Prosiding Seminar Nasional Bahasa Ibu 2024/2025, 2025)
This study is library research which focuses on micro linguistics. The main source of the data is corpus Leipzig that gives big data in the form of Balinese language. The technique of collection uses simple random sampling. In the making of this paper, the main theory used to comprehend the finding is proposed by (Kroeger, 2005) however some of the phenomenon is elaborated with another theory proposed by fellow linguists. The result shows that verbs such in a dative case produce grammatical relation and semantic roles which have valence of two or three. Yet in specific cases for example in passive construction, it is occurred that valence reduction happens because of the agentive passive process, which refers to reduction of valence from 3 to 2. The grammatical relations found are Subject, Oblique, Adjunct, on the other hand semantic roles found are Agent, Theme, Locative (Goals, Source, In between), recipient, experiencer, and Stimulus. The theoretical purpose of the study is expected to be literature review for those who wish to pursue a micro linguistics major such as syntax, semantics, and morphology. Practically, this study is expected to be stimulus for preserving such an exotic Austronesian language which is the Balinese, and at the same time it is an attraction for foreign academic students.